Effect of Doping Element and Electrolyte’s pH on the Properties of Hydroxyapatite Coatings Obtained by Pulsed Galvanostatic Technique - Ungureanu, Elena; Vranceanu, Diana Maria; Vladescu, Alina; Parau, Anca Constantina; Tarcolea, Mihai; Cotrut, Cosmin Mihai (Coatings (Basel), 2021)
Hydroxyapatite (HAp) is the most widely used calcium phosphate as a coating on metal implants due to its biocompatibility and bioactivity. The aim of this research is to evaluate the effect of the pH’s electrolyte and doping element on the morphology, roughness, chemical, and phasic composition of hydroxyapatite-based coatings obtained by pulsed galvanostatic electrochemical deposition. As doping elements, both Sr and Ag were selected due to their good osseoinductive character and antibacterial effect, respectively. The electrolytes were prepared at pH 4 and 5, in which specific concentrations of Sr, Ag, and Sr + Ag were added. In terms of morphology, all coatings consist in ribbon-like crystals, which at pH 5 appear to be a little larger. Addition of Sr did not affect the morphology of HAp, while Ag addition has led to the formation of flower-like crystals agglomeration. When both doping elements were added, the flowers like agglomerations caused by the Ag have diminished, indicating the competition between Sr and Ag. X-Ray Diffraction analysis has highlighted that Sr and/or Ag have successfully substituted the Ca in the HAp structure. Moreover, at higher pH, the crystallinity of all HAp coatings was enhanced. Thus, it can be said that the electrolyte’s pH enhances to some extent the properties of HAp-based coatings, while the addition of Sr and/or Ag does not negatively impact the obtained features of HAp, indicating that by using pulsed galvanostatic electrochemical deposition, materials with tunable features dictated by the function of the coated medical device can be designed.